KUALITAS SUSTAINABILITY REPORT : DITINJAU DALAM PENERAPAN GREEN ACCOUNTING, STAKEHOLDERS PRESSURE, DAN KARATKERISTIK PERUSAHAAN - Nur Alfi Urfiah (2023)
This research was carried out to find out whether Green Accounting, Stakeholder Pressure consisted of Environmentally Sensitive Industries, Customer Proximity Industries, Employee Oriented Industries, and Investor Oriented Industries, as well as Company Characteristics that consisted of Liquidity and Firm Size have influence over Quality of Sustainability Report. The population of this study focuses on 45 companies that are members of the LQ45 on the Indonesia Stock Exchange (IDX) in the period of 2018 to 2022. Using the method of purposive sampling, there were 23 companies that met the criteria and were used as samples in this study. Sources of data used as a reference in this study come from sustainability reports, annual reports, and financial reports accessed through the official website of the company and the website of Indonesia Stock Exchange (IDX). This research is a secondary quantitative research using an analytical technique in the form of a multiple linear regression model with a significance level of 5% which is processed using STATA 14. The results of this study state that the variable of Environmentally Sensitive Industries have a significant positive effect on the Quality of Sustainability Report, variable of Green Accounting and Investor Oriented Industries have a negative significant effect on the Quality of Sustainability Report, while variable of Customer Proximity Industries, Employee Oriented Industries, Liquidity and Firm Size has no significant effect on the Quality of Sustainability Report.